Pests and fungal pathogens associated with Douglas fir stands showing crown defoliation and vitality loss - Gitta Jutta Langer; Johanna Bußkamp; Sandra Peters; Jenny Wietschorke; Jörg Grüner; Janina Faust; Dominik Wonsack (Journal für Kulturpflanzen)
Over the past decade, and particularly since the drought years 2018–2022, significant vitality losses have been observed in German Douglas fir stands. The epicentre of this damage was in Central and South-West Germany. To determine the cause of the observed loss of vitality, this study examined Douglas firs in twelve 37–70 years old forest stands of varying vigour. Crown condition was assessed using the terrestrial forest damage inventory (TWI) method. Sampled trees were assessed on site for abiotic and biotic damage. Needle, branch and stem samples were analysed using culture- and DNA-based methods to identify the associated fungal endophytes and pathogens. In the 48 Douglas firs studied, needle loss ranged from 0% to 90%. Contarinia spp., Nothophaeocryptopus gaeumannii and Heterobasidion annosum were observed in all the stands studied and were identified as the main biotic damaging factors along with the shoot dieback pathogens, which were detected in 38.9% of the trees.